Cerdas Finansial: Belajar Menabung untuk Membentuk Kemandirian Santri - Aptasari, Fety Widianti; Putri, Baiq Krisnina Maharani; Hastuti, Ely Windarti; Mujahidi, Khairul; Darmansyah, Satria; Adha, Rishan; Feryansyah (Department of Accounting, Faculty of Business and Economics, Universitas Islam Indonesia, 2025)
This community service program aims to enhance the financial literacy of students at Wasilatul Abror Islamic Boarding School in Central Lombok by fostering saving habits and basic financial planning skills. Financial literacy is an essential competency that should be instilled early to build responsible and independent individuals. The program was implemented in three stages: preparation, implementation, and evaluation. The implementation stage included delivering fundamental financial concepts, simulating personal budgeting, and practicing simple saving activities. The results indicate an improvement in students’ understanding and awareness of financial management. Students began to differentiate between needs and wants, allocate their pocket money more effectively, and set aside a portion for savings. The evaluation phase revealed positive changes in financial behavior and the development of basic life skills in money management. This program demonstrates that Islamic boarding schools can play a strategic role in embedding financial literacy and fostering students’ financial independence, preparing them to face future economic challenges.